A monitoring campaign (2013–2020) of ESA's Mars Express to study interplanetary plasma scintillation. (12th April 2023) - Kummamuru, P.; Molera Calvés, G.; Cimò, G.; Pogrebenko, S. V.; Bocanegra-Bahamón, T. M.; Duev, D. A.; Md Said, M. D.; Edwards, J.; Ma, M.; Quick, J.; Neidhardt, A.; de Vicente, P.; et al.
Abstract: The radio signal transmitted by the Mars Express (MEX) spacecraft was observed regularly between the years 2013–2020 at X-band (8.42 GHz) using the European Very Long Baseline Interferometry (EVN) network and University of Tasmania's telescopes. We present a method to describe the solar wind parameters by quantifying the effects of plasma on our radio signal. In doing so, we identify all the uncompensated effects on the radio signal and see which coronal processes drive them. From a technical standpoint, quantifying the effect of the plasma on the radio signal helps phase referencing for precision spacecraft tracking. The phase fluctuation of the signal was determined for Mars' orbit for solar elongation angles from 0 to 180 deg. The calculated phase residuals allow determination of the phase power spectrum. The total electron content of the solar plasma along the line of sight is calculated by removing effects from mechanical and ionospheric noises. The spectral index was determined as $-2.43 ± 0.11$ which is in agreement with Kolmogorov's turbulence. The theoretical models are consistent with observations at lower solar elongations however at higher solar elongation ( $>$ 160 deg) we see the observed values to be higher. This can be caused when the uplink and downlink signals are positively correlated as a result of passing through identical plasma sheets.